Anti-diabetic activity, characterization and derivation of proposed mechanism of action of pisoniaalba (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Diabetes mellitus is a chronic metabolic disorder that imposes a huge health and economic burden on societies. Because the currently available medications have many drawbacks, it is important to search for alternative therapies. Medicinal plants used in traditional medicines are ideal candidates. Hence, this study was undertaken to investigate the anti-diabetic activity of methanolic extract of Pisonia alba(MEPA). The antihyperglycemic activity was assessed using streptozotocin-induced diabetic model. Experimental diabetes was induced by a single intraperitoneal injection of streptozotocin at a dose of 150 mg/kg and animals with fasting blood glucose level (BGL) > 200 mg/dL were considered diabetic. Glibenclamide (5 mg/kg) was used as a standard drug. Fasting BGL and body weight were used to assess the antidiabetic activity; the characterization was performed using the different analytical techniques. The result was analyzed using GraphPad Prism software version 8 and one-way ANOVA followed by Tukey’s post hoc test with p< 0.05 considered as statistically significant. The MEPA (500 mg/kg) showed a significant BGL reduction in all the three animal models. MEPA showed a significant antihyperglycemic activity in STZ induced diabetic mice, hypoglycemic activity and improvement of oral glucose tolerance in normal animals. The findings of the study strongly are strong evidences for the anti-hyperglycemic potential of the MEPA. MEPAs antihyperglycemic activity by inhibiting the glycogenolytic pathway and by improving peripheral utilization of glucose by acting as insulin mimetic agent. The effect may be attributed to the presence of bio-actives such as scopoletin, coumarin, gallic acid, ellagic acid and epicatechin.